PENGATURAN BERINVESTASI ALAT PELEDAK DI INDONESIA DITINJAU DARI UNDANG-UNDANG NOMOR 25 TAHUN 2007 TENTANG PENANAMAN MODAL - Arif Budiman, Nyoman; Adiyaryani, Ni Nengah (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 04, Juni 2014, 2014)
In the fields of business invesment, three tyeps of business are business open field, closed business and business with requirement. Issue which is appointed is “Arragement Invest In Indonesia Explosive Divices Based On Law Number 25 Of 2007 discuss about Investment” The methodology used in this study is normative method, statue approach legislation. The legal basic for invesment in Indonesia is according to Law Number 25 of 2007 disscus about Investment (Law No. 25 of 2007) article 12 paragraf (2), namely explosive devices are prohibited to perform invested by all investor both of domestic investor and foreigen investor of entry into force of Law number 25 of 2007. It is based explosive divices are included in the class Negative List ofx Invesment (DNI) in the category closed for business sector of invesment.
Keywords: invesment, investors, explosive device, negative list of invesment